2009
DOI: 10.1074/jbc.m109.004531
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Domains of Leptospira Immunoglobulin-like Proteins Interact with Elastin and Tropoelastin

Abstract: Leptospira spp., the causative agents of leptospirosis, adhere to components of the extracellular matrix, a pivotal role for colonization of host tissues during infection. Previously, we and others have shown that Leptospira immunoglobulin-like proteins (Lig) of Leptospira spp. bind to fibronectin, laminin, collagen, and fibrinogen. In this study, we report that Leptospira can be immobilized by human tropoelastin (HTE) or elastin from different tissues, including lung, skin, and blood vessels, and that Lig pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
143
0
16

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(165 citation statements)
references
References 52 publications
6
143
0
16
Order By: Relevance
“…LigB binds to Fn, fibrinogen, laminin, elastin, proelastin, and collagen and hence probably plays a substantial role in adhesion for pathogenic Leptospira (13,14,44,45). We have shown that LigBCen2 strongly binds to the NTD and weakly binds to the GBD of Fn (14) (NTD, K D ϭ 272 nM; GBD, K D ϭ 1200 nM).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LigB binds to Fn, fibrinogen, laminin, elastin, proelastin, and collagen and hence probably plays a substantial role in adhesion for pathogenic Leptospira (13,14,44,45). We have shown that LigBCen2 strongly binds to the NTD and weakly binds to the GBD of Fn (14) (NTD, K D ϭ 272 nM; GBD, K D ϭ 1200 nM).…”
Section: Discussionmentioning
confidence: 99%
“…Also, a non-immunoglobulin-like repeat region found on the C-terminal tail of LigB is not found in LigA (10 -12). Lig proteins are categorized as microbial surface components recognizing adhesive matrix molecules (MSCRAMMs) 2 due to their ability to bind to eukaryotic cells (13) through their interactions with extracellular matrix components, including fibronectin (Fn), laminin, collagens, elastin, and tropoelastin (13,14,45). Previously, a high affinity Fn-binding region was localized to LigBCen2, which includes the partial eleventh and complete twelfth immunoglobulin-like repeat region and the first 47 amino acids of the non-repeat regions of LigB (15).…”
mentioning
confidence: 99%
“…The cell-free extract was loaded onto a 10-ml nickel-nitrilotriacetic acid or GST column that was equilibrated with PBS. The protein purification procedures were the same as described previously (27,28).…”
Section: Methodsmentioning
confidence: 99%
“…Protein Binding Assays by ELISA-To measure the binding affinity of MAP Ag85 (Ag85A, Ag85B, and Ag85C) to Fn, human plasma Fn (0.5 g) was coated on microtiter plate wells using 0.1 M NaHCO 3 (pH 9.3) coating buffer at 4°C for overnight and blocked by PBS plus 3% BSA at 37°C for 1 h. Subsequently, various concentrations (0.1, 0.2, 0.4, 0.8, and 1.6 M) of His-tagged MAP Ag85 were added to each well and incubated at 37°C for 1 h. After three washes with PBST (PBS plus 0.05% Tween 20), bound Ag85 was detected by mouse anti-histidine (1:1000) and HRP-conjugated goat anti-mouse IgG (1:1000), serving as primary and secondary antibodies, respectively (27,28). To investigate the MAP Ag85B-binding domains of Fn, 0.5 g of full-length Fn, four Fn proteolytic domains (including NTD, GBD, CBD, and 40-kDa domain) or BSA (negative control) was coated on microtiter plate wells.…”
Section: Methodsmentioning
confidence: 99%
“…In FnBPA, the FBD1-2 region was shown to display adhesion properties against elastin in addition to fibronectin (Keane et al, 2007). In LigB, the Ig-like repeats are involved in chargecharge interactions with elastin (Lin et al, 2009). While structure-function analysis is awaited, OmpL37 demonstrates a pronounced specificity for elastin (Pinne et al, 2010).…”
Section: Elastin and Elastin-binding Proteinsmentioning
confidence: 99%